A Comprehensive Review of Literature on Endometriosis: Pathophysiology, Diagnosis, and Management - Ritu; Anshika Rosha (International Journal of Midwifery Nursing And Practices, 2025)
The endometrium, a tissue that resembles the lining of the uterus, develops outside the uterus in endometriosis, a chronic and frequently painful illness. Other parts of the body may also be affected, however the ovaries, fallopian tubes, and the tissue lining the pelvis are the most frequently affected. Infertility, heavy menstrual flow, and pelvic pain are the main signs of endometriosis, though each person may experience these symptoms to varying degrees. Although the exact cause of endometriosis is unknown, numerous factors are thought to play a role, including immune system dysfunction, retrograde menstruation, genetic predisposition, and hormonal influences, especially estrogen, which appear to be important in the development and persistence of endometriosis. Research indicates that the immune system may not recognize and destroy the displaced endometrial tissue, allowing it to grow outside the uterus. In order to diagnose endometriosis, a combination of imaging techniques, clinical examination, and laparoscopic surgery, which enables direct visualization and biopsy of the lesions, is frequently used. Due to the intricacy and fluctuation of symptoms, diagnosis can be difficult, and many women encounter delays in getting the care they need.
Keywords: Infertility; chronic pain; endometrial tissue; endometriosis; pelvic pain; retrograde menstruation